Size-dependent scattering efficiency in dye-sensitized solar cell - Koo, Hyung-Jun; Park, Jihee; Yoo, Beomjin; Yoo, Kicheon; Kim, Kyoungkon; Park, Nam-Gyu (ELSEVIER SCIENCE SA, 2008)
Effect of scattering particle size on light scattering efficiency in dye-sensitized solar cell has been investigated with a FTO/semitransparent nano-TiO2 layer (main-layer)/scattering layer (overlayer) structure, where two different rutile TiO2 particles of 0.3 mu m (G1) and 0.5 mu m (G2) were used for a scattering overlayer and 20-nm anatase particle for nano-TiO2 main-layer. The conversion efficiency of 7.55% for the 7 mu m-thick main-layer film is improved to 8.94% and 8.78% when G1 and G2 particulate overlayers are introduced, respectively, corresponding to 18.4% and 16.3% increments. While the conversion efficiency of the 14 mu m-thick main-layer is slightly improved from 8.60% to 9.09% and 9.15% upon depositing G1 and G2 particulate overlayers, respectively. Significant improvement and strong size-dependence upon deposition of scattering overlayer on the relatively thinner TiO2 main-layer film are associated with the quantity and wavelength of transmitted light and the difference in reflectivity of G1 and G2 scattering particles. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: LIGHT-SCATTERING; MULTIPLE-SCATTERING; ELECTRODES; RECOMBINATION; SIMULATIONS; PARTICLES; TITANIA; RUTILE; FILMS